Geopolitics, aid and growth - Dreher, Axel; Eichenauer, Vera; Gehring, Kai (CESifo working papers, 2013)
We investigate the effects of short-term political motivations on the effectiveness of foreign aid. Donor countries ́political motives might reduce the effectiveness of conditionality, channel aid to inferior projects or affect the way aid is spent in other ways, reduce the aid bureaucracyś effort, and might impact the power structure in the recipient country. We investigate whether geopolitical motives matter by testing whether the effect of aid on economic growth is reduced by the share of years a country has served on the United Nations Security Council (UNSC) in the period the aid has been committed, which provides quasi-random variation in commitments. Our results show that the effect of aid on growth is significantly lower when aid has been granted for political reasons. We derive two conclusions from this. First, short-term political favoritism reduces growth. Second, political interest variables are invalid instruments for aid, raising doubts about a large number of results in the aid effectiveness literature.
Literaturverz. S. 35 - 42